Thyroid Hormone Plays an Important Role in Cardiac Function: From Bench to Bedside - Yamakawa, Hiroyuki; Kato, Tomoko S.; Noh, Jaeduk Yoshimura; Yuasa, Shinsuke; Kawamura, Akio; Fukuda, Keiichi; Aizawa, Yoshiyasu (Frontiers in Physiology, 2021)
Thyroid hormones (THs) are synthesized in the thyroid gland, and they circulate in the blood to regulate cells, tissues, and organs in the body. In particular, they exert several effects on the cardiovascular system. It is well known that THs raise the heart rate and cardiac contractility, improve the systolic and diastolic function of the heart, and decrease systemic vascular resistance. In the past 30 years, some researchers have studied the molecular pathways that mediate the role of TH in the cardiovascular system, to better understand its mechanisms of action. Two types of mechanisms, which are genomic and non-genomic pathways, underlie the effects of THs on cardiomyocytes. In this review, we summarize the current knowledge of the action of THs in the cardiac function, the clinical manifestation and parameters of their hemodynamics, and treatment principles for patients with hyperthyroid- or hypothyroid-associated heart disease. We also describe the cardiovascular drugs that induce thyroid dysfunction and explain the mechanism underlying the thyroid toxicity of amiodarone, which is considered the most effective antiarrhythmic agent. Finally, we discuss the recent reports on the involvement of thyroid hormones in the regulation of myocardial regeneration and metabolism in the adult heart.